Canonical and Novel Non-Canonical Cholinergic Agonists Inhibit ATP-Induced Release of Monocytic Interleukin-1β via Different Combinations of Nicotinic Acetylcholine Receptor Subunits α7, α9 and α10 - Zakrzewicz, Anna; Richter, Katrin; Agné, Alisa; Wilker, Sigrid; Siebers, Kathrin; Fink, Bijan; Krasteva-Christ, Gabriela; Althaus, Mike; Padberg, Winfried; Hone, Arik J.; McIntosh, J. Michael; Grau, Veronika (Frontiers in Cellular Neuroscience, 2017)
Recently, we discovered a cholinergic mechanism that inhibits the adenosine triphosphate (ATP)-dependent release of interleukin-1β (IL-1β) by human monocytes via nicotinic acetylcholine receptors (nAChRs) composed of α7, α9 and/or α10 subunits. Furthermore, we identified phosphocholine (PC) and dipalmitoylphosphatidylcholine (DPPC) as novel nicotinic agonists that elicit metabotropic activity at monocytic nAChR. Interestingly, PC does not provoke ion channel responses at conventional nAChRs composed of subunits α9 and α10. The purpose of this study is to determine the composition of nAChRs necessary for nicotinic signaling in monocytic cells and to test the hypothesis that common metabolites of phosphatidylcholines, lysophosphatidylcholine (LPC) and glycerophosphocholine (G-PC), function as nAChR agonists. In peripheral blood mononuclear cells from nAChR gene-deficient mice, we demonstrated that inhibition of ATP-dependent release of IL-1β by acetylcholine (ACh), nicotine and PC depends on subunits α7, α9 and α10. Using a panel of nAChR antagonists and siRNA technology, we confirmed the involvement of these subunits in the control of IL-1β release in the human monocytic cell line U937. Furthermore, we showed that LPC (C16:0) and G-PC efficiently inhibit ATP-dependent release of IL-1β. Of note, the inhibitory effects mediated by LPC and G-PC depend on nAChR subunits α9 and α10, but only to a small degree on α7. In Xenopuslaevis oocytes heterologously expressing different combinations of human α7, α9 or α10 subunits, ACh induced canonical ion channel activity, whereas LPC, G-PC and PC did not. In conclusion, we demonstrate that canonical nicotinic agonists and PC elicit metabotropic nAChR activity in monocytes via interaction of nAChR subunits α7, α9 and α10. For the metabotropic signaling of LPC and G-PC, nAChR subunits α9 and α10 are needed, whereas α7 is virtually dispensable. Furthermore, molecules bearing a PC group in general seem to regulate immune functions without perturbing canonical ion channel functions of nAChR.